2011
DOI: 10.1016/j.mcn.2011.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like transcription factors in the nervous system: Novel players in neurite outgrowth and axon regeneration

Abstract: The Krüppel-like family of transcription factors (KLFs) have been widely studied in proliferating cells, though very little is known about their role in post-mitotic cells, such as neurons. We have recently found that the KLFs play a role in regulating intrinsic axon growth ability in retinal ganglion cells (RGCs), a type of central nervous system (CNS) neuron. Previous KLF studies in other cell types suggest that there may be cell-type specific KLF expression patterns, and that their relative expression allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 120 publications
1
81
0
Order By: Relevance
“…In particular, many of these studies have focused on the Krueppel-like factor (KLF) family of transcription factors, which have been shown to regulate the growth competency of RGCs and other CNS neurons 131133 . Interestingly, examination of sequence similarity among KLF family members showed that those that share a high degree of sequence similarity also have similar effects on regeneration 131 .…”
Section: Transcriptional Changesmentioning
confidence: 99%
“…In particular, many of these studies have focused on the Krueppel-like factor (KLF) family of transcription factors, which have been shown to regulate the growth competency of RGCs and other CNS neurons 131133 . Interestingly, examination of sequence similarity among KLF family members showed that those that share a high degree of sequence similarity also have similar effects on regeneration 131 .…”
Section: Transcriptional Changesmentioning
confidence: 99%
“…There are seventeen KLF genes in mammals that group into three major subfamilies based on similarities in their N-terminal domains (Figure 1) [49]. Krüppel-like factors 3, 8, and 12 (Group 1) typically repress gene transcription by binding to the C-terminal binding proteins (CtBPs), a family of transcriptional repressors that recruit chromatin-modifying enzymes that add repressive marks to histones [80].…”
Section: 2 Krüppel-like Factorsmentioning
confidence: 99%
“…For example, KLF9 activates the Fgfr1 promoter in proliferating myoblasts but represses it in differentiated myotubes via the same DNA binding site [48]. Krüppel-like factors 5, 15 and 17 do not group into any of the other families based on the presence of identifiable protein-protein interaction motifs, although their primary amino acid sequences place KLFs 15 and 17 closer to Group 3, and KLF5 closer to Group 1 [47, 49]. All three can act as activators or repressors of transcription [25, 52, 82](and see section 3.3 ), In some cases, KLFs of the same subfamily have overlapping or redundant functions and can compensate for each other if one is lost or deleted [28, 85].…”
Section: 2 Krüppel-like Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…KLFs are highly distributed in various neural cells in the brain and have been implicated in a variety of human neurological diseases (Moore et al, 2009; Moore et al, 2011). Within this review, we will focus on recent advances describing the role and mechanisms of KLFs in neurological disorders, with a focus on ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%